2017
DOI: 10.15294/kreano.v8i2.7192
|View full text |Cite
|
Sign up to set email alerts
|

Proses Berpikir Kritis Siswa SMA dalam Pengajuan Soal Matematika Berdasarkan Tingkat Kemampuan Matematika

Abstract: Penelitian ini bertujuan untuk mendeskripsikan proses berpikir kritis siswa SMA dalam pengajuan soal matematika berdasarkan tingkat kemampuan matematika yang terdiri atas kemampuan matematika tinggi, sedang dan rendah. Subjek penelitian adalah siswa kelas X dan berjumlah lima orang. Adapun hasil penelitian yang menggambarkan proses berpikir kritis siswa SMA dalam pengajuan soal berdasarkan tingkat kemampuan matematika sebagai berikut. 1) Siswa berkemampuan matematika tinggi kategori baik dalam pengajuan soal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…Ennis, Baron and Sternberg defines critical thinking as reflective thinking that is grounded and focused on establishing what to believe or what to do, while Langrehr stated that critical thinking is evaluative thinking involving the relevant criteria in accessing information along with accuracy, relevance, confidence , constancy, and bias (Sumarmo, 2015).Another opinion, Glaser (Permana & Sumarmo, 2007) states that Mathematical critical thinking contains abilities and dispositions combined with knowledge, mathematical reasoning abilities, and cognitive strategies that were previously used to generalize, prove, assess reflective mathematical situations'. In line with that, (Men, 2017) argues that critical thinking is reasonable and reflective thinking that is carried out systematically on all information or problems obtained so that it can make the right decisions. The purpose of critical thinking is to achieve deep understanding.…”
Section: Introductionmentioning
confidence: 94%
“…Ennis, Baron and Sternberg defines critical thinking as reflective thinking that is grounded and focused on establishing what to believe or what to do, while Langrehr stated that critical thinking is evaluative thinking involving the relevant criteria in accessing information along with accuracy, relevance, confidence , constancy, and bias (Sumarmo, 2015).Another opinion, Glaser (Permana & Sumarmo, 2007) states that Mathematical critical thinking contains abilities and dispositions combined with knowledge, mathematical reasoning abilities, and cognitive strategies that were previously used to generalize, prove, assess reflective mathematical situations'. In line with that, (Men, 2017) argues that critical thinking is reasonable and reflective thinking that is carried out systematically on all information or problems obtained so that it can make the right decisions. The purpose of critical thinking is to achieve deep understanding.…”
Section: Introductionmentioning
confidence: 94%
“…Hal tersebut disebabkan oleh strategi pembelajaran yang diterapkan belum mengembangkan berpikir tingkat tinggi. Mengevaluasi proses berpikir kritis peserta didik bukanlah hal mudah bagi pendidik (Men, 2017;Septyani & Siswono, 2018). Hal tersebut dikemukakan oleh Rasiman (2013) bahwa kenyataan di lapangan tidak mudah mengetahui proses berpikir kritis melalui pembelajaran matematika karena guru lebih fokus pada hasil belajar peserta didik.…”
Section: Pendahuluanunclassified
“…In general, the profiles of students' critical thinking processes were different. Previous research has shown that there were differences in students' critical thinking processes in solving math problems [20], [21]. Of course, many factors influence these differences, including cognitive style and gender.…”
Section: Female Students With Field Dependent Cognitive Style (Fd)mentioning
confidence: 99%